Lack of MEF2A Δ7aa mutation in Irish families with early onset ischaemic heart disease, a family based study - Horan, Paul G (BioMed Central, 2006)
BACKGROUND: Ischaemic heart disease (IHD) is a complex disease due to the combination of environmental and genetic factors. Mutations in the MEF2A gene have recently been reported in patients with IHD. In particular, a 21 base pair deletion (Δ7aa) in the MEF2A gene was identified in a family with an autosomal dominant pattern of inheritance of IHD. We investigated this region of the MEF2A gene using an Irish family-based study, where affected individuals had early-onset IHD. METHODS: A total of 1494 individuals from 580 families were included (800 discordant sib-pairs and 64 parent-child trios). The Δ7aa region of the MEF2A gene was investigated based on amplicon size. RESULTS: The Δ7aa mutation was not detected in any individual. Variation in the number of CAG (glutamate) and CCG (proline) residues was detected in a nearby region. However, this was not found to be associated with IHD. CONCLUSION: The Δ7aa mutation was not detected in any individual within the study population and is unlikely to play a significant role in the development of IHD in Ireland. Using family-based tests of association the number of tri-nucleotide repeats in a nearby region of the MEF2A gene was not associated with IHD in our study group.